PROSPECTS FOR THE DEVELOPMENT OF STRATEGIC DECISIONS FOR UZBEKISTAN, DRAWN FROM INTERNATIONAL PRACTICES - Muratova Charos Alimjanovna (European Science Publishing, 2025)
This article explores the prospects for the development of strategic decision-making in Uzbekistan, drawing insights from successful international practices. As Uzbekistan continues its economic transformation and integration into the global market, effective strategic planning becomes crucial for sustaining growth and enhancing competitiveness. By examining various international case studies and governance frameworks, this paper identifies key factors that influence successful strategic decisions and proposes a tailored approach for Uzbekistan. The discussion highlights the importance of stakeholder engagement, data-driven decision-making, and the integration of innovative practices to leverage the country's unique advantages while addressing its challenges.
Keywords: Strategic decisions, Uzbekistan, international practices, stakeholder engagement, data-driven decision-making, economic transformation, governance frameworks